Movement System Diagnoses for Balance Dysfunction: Recommendations From the Academy of Neurologic Physical Therapy's Movement System Task Force. Issue 9 (21st June 2021) - Gill-Body, Kathleen M; Hedman, Lois D; Plummer, Laura; Wolf, Leslie; Hanke, Timothy; Quinn, Lori; Riley, Nora; Kaufman, Regina; Verma, Akanshka; Quiben, Myla; Scheets, Patricia
Abstract: : The movement system was identified as the focus of our expertise as physical therapists in the revised vision statement for the profession adopted by the American Physical Therapy Association in 2013. Attaining success with the profession's vision requires the development of movement system diagnoses that will be useful in clinical practice, research, and education. To date, only a few movement system diagnoses have been identified and described, and none of these specifically address balance dysfunction. Over the past 2 years, a Balance Diagnosis Task Force, a subgroup of the Movement System Task Force of the Academy of Neurologic Physical Therapy, focused on developing diagnostic labels (or diagnoses) for individuals with balance problems. This paper presents the work of the task force that followed a systematic process to review available diagnostic frameworks related to balance, identify 10 distinct movement system diagnoses that reflect balance dysfunction, and develop complete descriptions of examination findings associated with each balance diagnosis. A standardized approach to movement analysis of core tasks, the Framework for Movement Analysis developed by the Academy of Neurologic Physical Therapy Movement Analysis Task Force, was integrated into the examination and diagnostic processes. The aims of this perspective paper are to (1) summarize the process followed by the Balance Diagnosis Task Force to develop an initial set of movement system (balance) diagnoses; (2) report the recommended diagnostic labels and associated descriptions; (3) demonstrate the clinical decision-making process used to determine a balance diagnosis and develop a plan of care; and (4) identify next steps to validate and implement the diagnoses into physical therapist practice, education, and research. Impact: The development and use of diagnostic labels to classify distinct movement system problems is needed in physical therapy. The 10 balance diagnosis proposed can aid in clinical decision making regarding intervention.